The Behavioral Mechanisms of Voluntary Cooperation across Culturally Diverse Societies: Evidence from the US, the UK, Morocco, and Turkey - Till O. Weber; Jonathan F. Schulz; Benjamin Beranek; Fatima Lambarraa-Lehnhardt; Simon Gaechter (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the role of cooperative preferences, beliefs, and punishments to uncover potential cross-societal differences in voluntary cooperation. Using one-shot public goods experiments in four comparable subject pools from the US and the UK (two similar Western societies) and Morocco and Turkey (two comparable non-Western societies), we find that cooperation is lower in Morocco and Turkey than in the UK and the US. Using the ABC approach – in which cooperative attitudes and beliefs explain cooperation – we show that cooperation is mostly driven by differences in beliefs rather than cooperative preferences or peer punishment, both of which are similar across the four subject pools. Our methodology is generalizable across subject pools and highlights the central role of beliefs in explaining differences in voluntary cooperation within and across culturally, economically, and institutionally diverse societies. Because our behavioral mechanisms correctly predict actual contributions, we argue that our approach provides a suitable methodology for analyzing the determinants of voluntary cooperation of any group of interest.
Keywords: C90; H40; C70; D20; 330; public goods; voluntary cooperation; ABC method; conditional cooperation; beliefs; punishment; cross-cultural experiments; WEIRD societies